Calcium carbonate, organic content and Calcium and Titanium counts of sediment core GIK16160-3 from Mozambique Margin - van der Lubbe, Jeroen (PANGAEA, 2022)
High-resolutions (1 cm) down-core profiles of XRF core-scanning Ca and Ti counts from sediment cores GIK16160-3, which was recovered from the Mozambique Margin at 1339 m water depth. The Ca and Ti records of GIK16160-3 represents proportional variations between marine calcium carbonate and terrestrial lithogenic sediment fractions were acquired using an Avaatech XRF core scanner at the Department of Marine Climate Research of Kiel University (Kiel, Germany) and at the Royal Netherlands Institute for Sea Research (Texel, the Netherlands). In addition, the calcium carbonate and organic contents (weight %) of GIK16160-3 were determined as replicates every 10 cm based on ~ 10 mg freeze-dried sediment powder using a CARLO ERBA Elemental Analyzer at the GEOMAR (Kiel, Germany).
Keywords: Calcium Carbonate content; Mozambique Channel; Organic content; XRF-Ca counts; XRF core scanner data; XRF-Ti counts